Penerapan Pembelajaran Kooperatif Tipe Gambar Dan Gambar Untuk Meningkatkan Motivasi Belajar Dan Keterampilan Menulis Teks Eksplanasi Siswa Kelas XI SMK - Sri Rahayu; Moh. Gufron (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to increase learning motivation and writing skills of Explanation Text in 2nd students of SMKN 1 Boyolangu by applying the cooperative learning method of picture and picture types. This research is a class action research (CAR) which was carried out in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were 2nd students of SMKN 1 Boyolangu, and there are 36 students. Sources of data in this study are informants and documents. Data collection techniques used are observation, interviews, tests, and documentation. Data validity uses data triangulation techniques, method triangulation, and informant reviews. Data analysis used descriptive comparative analysis technique. The research procedure is a spiral model that is interrelated. The results showed that the application of the cooperative learning method with picture and picture can increase motivation and skills in writing Explanation Text in 2 nd students of SMKN 1 Boyolangu from pre-action to cycle I and from cycle I to cycle II. This was indicated by an increasing in: (1) student motivation from cycle I to cycle II which was quite significant; (2) the average value of students' writing skills, namely from 49.09 in pre-action to 72.36 in cycle I, and 92.63 in cycle II.